Pemberdayaan Masyarakat Dukuh Kerep dan Krajan dalam Merealisasikan Unit Pelayana Zakat, Infaq, Shodaqoh - Suwardi Suwardi (Social Science Academic, 2023)
The problem of Padamulya Village community is that people do not understand about Zakat, Infaq, Sadaqoh, the community thinks that zakat is only on zakat fitrah and zakat maal in general, the community cannot distinguish between income already affected by zakat or still merely infaq , as well as alms, and there has been no grouping of the receipt of benefits from the collection of Zakat, Infaq, Sadaqoh,. And distribution is not yet programmed (planned and measured) according to the rules in the Qur'an and the Hadith. The aim in the implementation of Community Service (KPM ) in Dukuh Kerep and krajan, Pasirkuda District, Cianjur Regency is oriented to community development, achievement of planned socialization programs, enhancing community capacity in the economic field, namely on Zakat, Infaq, Shadaqoh, Wakaf The method is carried out in a participatory manner through lecture, question and answer methods and discussion on increasing knowledge about Zakat, Infaq, Sadaqoh,. As for the results of the socialization activities of Zakat, Infaq, Sadaqoh, is the understanding of the people who do not know yet become know. The implementation of this socialization activity showed that there was an increase in public knowledge about the importance of Zakat, Infaq, Shodaqoh, in improving the economy of the community especially in Dukuh Kerep and Krajan